2013
DOI: 10.1590/s1519-69842013000400015
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat use by three species of egret (Pelecaniformes, Ardeidae) in southern Brazil

Abstract: In the present study, we examined the role of different habitat components and their relationship with microhabitat use by three species of egret: Cocoi heron (Ardea cocoi), Great egret (Ardea alba), and Cattle egret (Bubulcus ibis), in wetlands of southern Brazil. Ardea alba and A. cocoi were not habitat-specific (e.g. vegetation cover and flooding level). Conversely, B. ibis was associated with drier microhabitats. Relative air humidity and air temperature were the main variables which correlated with the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This is alarming, as previous studies on foraging ecology (Gimenes and Anjos, ), microhabitat use (Pinto et al ., ) and breeding behaviour (Nunes and Tomas, ; Scherer et al ., ) have shown that the great egret in Brazil tends to occupy regions with very specific abiotic characteristics. In southern Brazilian wetlands, for example, the presence of this species is influenced by precise air temperature and relative humidity levels, which affect foraging patterns due to reduced prey availability on hotter days (Pinto et al ., ). Thus, changes in the major environmental variables of the wetlands used by the great egret are likely to exert an influence on population dynamics.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is alarming, as previous studies on foraging ecology (Gimenes and Anjos, ), microhabitat use (Pinto et al ., ) and breeding behaviour (Nunes and Tomas, ; Scherer et al ., ) have shown that the great egret in Brazil tends to occupy regions with very specific abiotic characteristics. In southern Brazilian wetlands, for example, the presence of this species is influenced by precise air temperature and relative humidity levels, which affect foraging patterns due to reduced prey availability on hotter days (Pinto et al ., ). Thus, changes in the major environmental variables of the wetlands used by the great egret are likely to exert an influence on population dynamics.…”
Section: Introductionmentioning
confidence: 97%
“…Although this species is globally listed as ‘least concern’ by the International Union for Conservation of Nature (IUCN, ), with trends indicating increasing populations (Morales, ), it is increasingly affected by the many threats to the wetlands in which it forages, roosts and breeds. This is alarming, as previous studies on foraging ecology (Gimenes and Anjos, ), microhabitat use (Pinto et al ., ) and breeding behaviour (Nunes and Tomas, ; Scherer et al ., ) have shown that the great egret in Brazil tends to occupy regions with very specific abiotic characteristics. In southern Brazilian wetlands, for example, the presence of this species is influenced by precise air temperature and relative humidity levels, which affect foraging patterns due to reduced prey availability on hotter days (Pinto et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Gimenes and Anjos (2011), A. cocoi, A. alba and T. lineatum did not demonstrate a clear preference for a particular habitat of the Paraná River, whereas Pinto et al (2013) reported that A. cocoi and A. alba used similar substrates in the presence or absence of water. This results differ from ours, since in our data these species showed preference for aquatic macrophytes in the four phases of the seasonal cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of habitats by these birds can vary considerably according to their degree of specialization (Dimalexis et al 1997, Bancroft et al 2002, Isacch and Martínez 2003. While some species use various types of habitats, others are strongly associated with a particular habitat or microhabitat (Accordi and Hartz 2006, Gimenes and Anjos 2011, Alves et al 2012, Pinto et al 2013.…”
Section: Introductionmentioning
confidence: 99%